Two weeks notice [videorecording (DVD)] - Bullock, Sandra; Lawrence, Marc, 1959-; Grant, Hugh (Warner Home Video, 2003)
Lucy Kelson, Chief Counsel for the Wade Corporation, one of New York City's top commercial real estate developers. She's a brilliant lawyer with a sharp, strategic mind. She also has an ulcer and doesn't get much sleep. It's not the job that's getting to her. It's her millionaire boss, George Wade. Handsome, charming and undeniably self-absorbed, he treats her more like a nanny than a Harvard Law grad and can barely choose a tie without her help. Now, after five years of calling the shots on everything from his clothes to his divorce settlements, Lucy Kelson is calling it quits.